2015
DOI: 10.5137/1019-5149.jtn.16193-15.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of initial systemic inflammatory response after aneurysmal subarachnoid hemorrhage

Abstract: ABSTRACTcytokines such as interleukin-6 (IL-6) and C-reactive protein (CRP) would increase early after SAH, inflammatory response would have been involved in the course of EBI. So far, most recent studies on inflammatory cytokines in SAH have focused on DCV while fewer studies have focused on EBI and its complications such as pneumonia, which influence the clinical course of aneurysmal SAH. Clinically, a serious initial clinical grade usually indicates a severe EBI after SAH (15), and infection is usually asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…First, the two groups of authors conducted their study in mixed populations of patients, containing both ruptured and unruptured aneurysms. This seems important to indicate, as the SAH is a separate pathological entity with serious consequences, also including an aspect of cytokine release, such as cerebral vasospasm [ 29 , 42 , 43 ]. Admittedly, both groups of authors have separated a subgroup of unruptured aneurysms, but after this maneuver the resulting number of their material became smaller than ours (15 and 10 patients, respectively, in relation to our 25 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the two groups of authors conducted their study in mixed populations of patients, containing both ruptured and unruptured aneurysms. This seems important to indicate, as the SAH is a separate pathological entity with serious consequences, also including an aspect of cytokine release, such as cerebral vasospasm [ 29 , 42 , 43 ]. Admittedly, both groups of authors have separated a subgroup of unruptured aneurysms, but after this maneuver the resulting number of their material became smaller than ours (15 and 10 patients, respectively, in relation to our 25 patients).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the animal models, there are only scarce data pertaining to aneurysms in humans [ 27 , 28 ]. It should be also noted that studies carried out on clinical material of aneurysms after subarachnoid hemorrhage (SAH) may result in rather confusing conclusions as to the problem of primary aneurysm formation and growth [ 29 ]. The hitherto published studies were based on sampling blood for the presence of the cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing number of scholars believe that SAH is closely related to the body's inflammatory response. They think that the occurrence and development of SAH are also associated with the body's cytokine expression ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 126 130 ] C-reactive protein (CRP) was shown to be increased in several studies, peaking at 73–96 hours, and correlated with worse EBI. [ 43 76 157 ] In another study, high-sensitivity CRP (hs-CRP), which is a more precise measure of CRP, was found to be significantly associated with poor outcomes determined by Glasgow Outcome Scale at 3 months. [ 126 ] Zhong et al .…”
Section: Introductionmentioning
confidence: 99%
“…showed that higher levels of IL-6 and IL-10 24 hours after admission is associated with severe EBI, and increased the susceptibility to infections such as pneumonia. [ 157 ] The rate of change of IL-6 and erythrocyte sedimentation rate (ESR) levels were also associated with DCI. [ 87 ] Red blood cell distribution width (RDW), an emerging inflammatory marker, was also found to be significantly higher in SAH patients and associated with poor outcome.…”
Section: Introductionmentioning
confidence: 99%